Peran Keterlibatan Orangtua dan Regulasi Diri Dalam Belajar Terhadap Prokrastinasi Akademik Siswa - Doranangtiyasko, Alfil; , Dr. Sri Lestari, S.Psi.,M.Si; , Dr. Nanik Prihartanti, M.Si (2016)
Academic procrastination is a delay which is done repeatedly and intentionally by performing other activities that are not required in academic tasks (Tan, 2008). The purpose of this study was to empirically demonstrate the role of parents involvement and self-regulation in learning to students' academic procrastination. This research applied quantitative approach. Samples of this study involved 276 students of class students X, XI, XII, consisting of, 110 male students and 166 female students. Measurement scales used were parents' involvement, self-regulation in learning and academic parents procrastination scale. The results showed that parents' academic involvement and self-regulation in learning parents contribute 32% to academic procrastination. Self-regulation in learning came up to be stronger predictor than parents' involvement. The implication of this research is to prevent parents academic parents procrastination, means that the educational institutions need to improve the parents students' self regulation in learning and encourage parents to be more students involved in students learning.